2022
DOI: 10.3390/children9060890
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Arts-Based Evidence from Children Participating in a Pilot Randomised Controlled Study of School-Based Arts Therapies

Abstract: (1) Background: There is limited evidence on the impact of arts therapies as a tool for the prevention of mental health difficulties in childhood. This pilot randomised controlled study aimed to investigate the impact of arts therapies on children’s mental health and well-being; the qualitative and arts-based evidence is presented in this article. (2) Methods: Sixty-two children (aged 7–10) with mild emotional and behavioral difficulties were recruited across four primary schools and were randomly assigned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Furthermore, similar to other members of school social support teams (e.g., social workers, psychologists) who typically have dedicated physical spaces, we advocate for a featured SBDT space within the school, or on school grounds, that is set up to flexibly engage children in dramatic play (Mayor & Frydman, 2021 ; Webb, 2019 ). This suggestion has been previously expressed by scholars in the field (Danieli et al, 2019 ; Moula et al, 2022 ; Regev et al, 2015 ), and would ideally serve to reduce reported experiences of instability among SBDT practitioners (Frydman & Mayor, 2021 ), thereby supporting ecological integration into the setting.…”
Section: Recommendationsmentioning
confidence: 64%
“…Furthermore, similar to other members of school social support teams (e.g., social workers, psychologists) who typically have dedicated physical spaces, we advocate for a featured SBDT space within the school, or on school grounds, that is set up to flexibly engage children in dramatic play (Mayor & Frydman, 2021 ; Webb, 2019 ). This suggestion has been previously expressed by scholars in the field (Danieli et al, 2019 ; Moula et al, 2022 ; Regev et al, 2015 ), and would ideally serve to reduce reported experiences of instability among SBDT practitioners (Frydman & Mayor, 2021 ), thereby supporting ecological integration into the setting.…”
Section: Recommendationsmentioning
confidence: 64%
“…Through combing and analyzing the related literature, it summarizes the wide application of EXAT and painting therapy in the fields of psychotherapy, rehabilitation nursing, education and other fields, as well as EXAT and painting therapy achieves significant therapeutic effects. For instance, in psychotherapy, EXAT or painting therapy has been shown to be useful in improving mental health, relieving stress and anxiety (Malchiodi, 2011), and improving self-acceptance (Moula et al, 2022). In the field of rehabilitative care, EXAT and painting therapy can help patients with pain and anxiety relief and distraction (Zhou, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…All these effects generate significant differences between dancers and non-dancers, which is why we recommend it as an educational resource for improving learning strategies. These effects can be complementary to the positive changes in children’s mental health well-being [ 39 ].…”
Section: Discussionmentioning
confidence: 99%